The Effect of Work Environment, Work Load, Work Discipline and Work Commitment on The Performance Employees of The Secretariat in Bondowoso Regency DPRD - Ira Sofiyanti; Muhammad Firdaus; Yuniorita Indah Handayani (ARTOKULO : Journal of Accounting, Economic and Management, 2024)
Performance measurement is still a topic that is often raised in research, as the focus of this research is examining the performance of Bondowoso Regency DPRD Secretariat employees. This research was developed with the aim of testing and analyzing the influence of the work environment, workload, work discipline and work commitment on the performance of Bondowoso Regency DPRD Secretariat employees. This research is included in confirmatory research with a sample size of 52 respondents, saturated sampling technique was used due to the limited number of employees. The data analysis technique used is Multiple Linear Regression processed with SPSS 22.0. Based on the results of data analysis, it shows that both partially and simultaneously the work environment variables, workload, work discipline and work commitment have a significant effect on the performance of employees of the Bondowoso Regency Community and Village Empowerment Service. The results of the coefficient of determination show that the work environment, workload, work discipline and work commitment have a contribution of 83.7% to the performance variable